Curvilinear Association Between Language Disfluency and FMR1 CGG Repeat Size Across the Normal, Intermediate, and Premutation Range - Klusek, Jessica; Porter, Anna; Abbeduto, Leonard; Adayev, Tatyana; Tassone, Flora; Mailick, Marsha R.; Glicksman, Anne; Tonnsen, Bridgette L.; Roberts, Jane E. (Frontiers in Genetics, 2018)
Historically, investigations of FMR1 have focused almost exclusively on the clinical effects of CGG expansion within the categories of the premutation (55-200 CGG repeats) and fragile X syndrome (>200 CGG repeats). However, emerging evidence suggests that CGG-dependent phenotypes may occur across allele sizes traditionally considered within the “normal” range. This study adopted an individual-differences approach to determine the association between language production ability and CGG repeat length across the full range of normal, intermediate, and premutation alleles. Participants included 61 adult women with CGG repeats within the premutation (n=37), intermediate (i.e., 41-54 repeats; n=2), or normal (i.e., 6-40 repeats; n=22) ranges. All participants were the biological mothers of a child with a developmental disorder, to control for the potential effects of parenting stress. Language samples were collected and the frequency of language disfluencies (i.e., interruptions in the flow of speech) served as an index of language production skills. Verbal inhibition skills, measured with the Hayling Sentence Completion Test, were also measured and examined as a correlate of language disfluency, consistent with theoretical work linking language disfluency with inhibitory deficits (i.e., the Inhibition Deficit Hypothesis). Blood samples were collected to determine FMR1 CGG repeat size. A general linear model tested CGG repeat size of the larger allele (allele-2) as the primary predictor of language disfluency, covarying for education level, IQ, age, and CGG repeats on the other allele. A robust curvilinear association between CGG length and language disfluency was detected, where low-normal ( <25 repeats) and mid-premutation alleles ( 90-110 repeats) were linked with higher rates of disfluency. Disfluency was not associated with inhibition deficits, which challenges prior theoretical work and suggests that a primary language deficit could account for elevated language disfluency in FMR1-associated conditions. Findings suggest CGG-dependent variation in language production ability, which was evident across individuals with and without CGG expansions on FMR1.